ROLE OF DIGITAL MARKETING IN INCREASING VISITORS INTEREST IN BANYUURIP TOURISM VILLAGE, KEDAMEAN, GRESIK - Feliks Anggia B.K Panjaitan; Hotman Panjaitan (Universitas Islam Lamongan, 2022)
In this digital age, marketers face new challenges and opportunities. Electronic media by marketers to promote products or services to the market is known as digital marketing. The primary goal of digital marketing is to attract customers and provide them with opportunities to interact with business owners or tourist attractions via digital media. The importance of digital marketing for marketers and consumers is the focus of this study. The impact of digital marketing and promotional strategies on increasing visitor interest was investigated. The effectiveness of digital marketing and its impact on increasing visitor interest were discussed in this study. The sample examined consisted of 150 respondents who were chosen at random to demonstrate the effectiveness of digital marketing. The information gathered was analyzed using a variety of statistical tools and techniques..